Relation of socioeconomic status to overweight and obesity: a large population-based study of Chinese adults - Hua Zhang; Hui Xu; Fei Song; Weili Xu; Stephanie Pallard-Borg; Xiuying Qi (Taylor & Francis Group, 2017)
Background: China has been going through significant changes in social and economical aspects and with great socioeconomic disparity in different regions. However, data on the association between socioeconomic status (SES) and obesity are not available in Tianjin, China. Aim: This study aimed to investigate the association between SES and high adiposity among the adult population in Tianjin. Subjects and methods: A total of 7351 individuals aged 20-79 were included in this study. Socioeconomic information was collected through an interview following a structured questionnaire. Waist circumference, body weight and height were measured following standard procedures. Overweight and obesity were defined according to the criteria of the Working Group on Obesity in China. Data were analysed using multinomial logistic regression with adjustment for potential confounders. Results: Stratified analysis showed that higher monthly income and education were related to decreased odds of abdominal overweight/obesity in women, while high education was associated with increased odds of general overweight/obesity in men. Retirement increased the odds of abdominal overweight and obesity and non-manual work was associated with low odds of abdominal obesity in women. Conclusions: SES was associated with general and abdominal overweight/obesity and sex may play a role in such an association.